Assessing the benefits of the “Intergalactic World” social emotional learning program for 8–12-year-old children in Portugal: perspectives from teachers and caregivers - Antunes, Rita; Alexandre, Joana; Guedes, Maryse; Filipe, Marisa G.; Veríssimo, Manuela (Frontiers in Psychology, 2023)
'Intergalactic World' is a new social-emotional program designed to reduce psychopathological symptoms and improve social and emotional skills in children aged 8 to 12 (Antunes et al., 2022). This study aims to evaluate the program's benefits from teachers' and caregivers' perspectives, focusing on internalizing and externalizing behaviors. The findings were obtained through self-reported measures using a pretest-posttest design with a follow-up period, with no control group. One hundred fifty-four children (M age = 9.66, SD = 0.78) participated in this intervention study. Eleven teachers completed the Teacher's Report Form (TRF) for these children, and 133 caregivers completed the Child Behavior Checklist (CBCL). Participants without caregivers' reports were excluded from the analysis. Data were collected at three-time points: before the intervention (T1), immediately after (T2), and six months after the implementation of the program (T3). Results showed an effect of time on the Internalization scores (at T3 for teachers and T2 and T3 for caregivers) with no gender effect and a decrease in the perception of externalizing behaviors with a gender effect: Boys were perceived as exhibiting more externalizing behaviors than girls. However, these behaviors significantly decrease at T3 for teachers and at T2 and T3 for caregivers. Despite its limitations, this study highlights the benefits of employing social-emotional programs to help reduce children’s internalizing and externalizing behaviors. A multi-informant approach enables a comprehensive analysis and provides insights into the child's significant contexts and interactions with adults.